Antitumor agent 25-epi Ritterostatin G(N)1(N) induces endoplasmic reticulum stress and autophagy mediated cell death in melanoma cells - Ahmed, Kausar Begam Riaz (Int J Oncol, 2017)
Metastatic melanoma is the most aggressive of all skin cancers and is associated with poor prognosis owing to lack of effective treatments. 25-epi Ritterostatin G(N)1(N) is a novel antitumor agent with yet undefined mechanisms of action. We sought to delineate the antitumor mechanisms of 25-epi Ritterostatin G(N)1(N) in melanoma cells to determine the potential of this compound as a treatment for melanoma. Activation of the endoplasmic reticulum (ER) stress protein glucose-regulated protein 78 (GRP78) has been associated with increased melanoma progression, oncogenic signaling, drug resistance, and suppression of cell death. We found that 25-epi Ritterostatin G(N)1(N) induced cell death in melanoma cells at nanomolar concentrations, and this cell death was characterized by inhibition of GRP78 expression, increased expression of the ER stress marker CHOP, loss of mitochondrial membrane potential, and lipidation of the autophagy marker protein LC3B. Importantly, normal melanocytes exhibited limited sensitivity to 25-epi Ritterostatin G(N)1(N). Subsequent in vivo results demonstrated that 25-epi Ritterostatin G(N)1(N) reduced melanoma growth in mouse tumor xenografts and did not affect body weight, suggesting minimal toxicity. In summary, our findings indicate that 25-epi Ritterostatin G(N)1(N) causes ER stress and massive autophagy, leading to collapse of mitochondrial membrane potential and cell death in melanoma cells, with minimal effects in normal melanocytes. Thus, 25-epi Ritterostatin G(N)1(N) is a promising anticancer agent that warrants further investigation.